Education of People Working in Poland Versus Other European Union Countries - Kwiatkowska, Walentyna (Olsztyn Economic Journal, 2017)
Education plays a special role in the construction of a modern knowledge-based economy. The increase in the educational level of the population is a chance for a faster social and economic development of any economy. The level of education also determines the quality of the individual and is important for their position in the labor market. The aim of this study is to show the role of education in shaping employment in Poland compared to other European Union countries in the years 2005–2014. The analysis makes it possible to positively assess qualitative changes in the structure of the employment stock in Poland. In the period under study, the share of employees with low educational attainment decreased in a fundamental way, while the share of employees with higher education increased significantly.